Interactive digital interventions to promote self-management in adults with asthma: systematic review and meta-analysis. - McLean, G; Murray, E; Band, R; Moffat, K; Hanlon, P; Bruton, A; Thomas, M; Yardley, L; Mair, F (BioMed Central, 2016)
Background To identify, summarise and synthesise the evidence for using interactive digital interventions to support patient self-management of asthma, and determine their impact. Methods Systematic review with meta-analysis. We searched MEDLINE, EMBASE, CINAHL, PsycINFO, ERIC, Cochrane Library, DoPHER, TROPHI, Social Science Citation Index and Science Citation Index. The selection criteria requirement was studies of adults (16 years and over) with asthma, interventions that were interactive digital interventions andthe comparator was usual care. Outcomes were change in clinical outcomes, cost effectiveness and patient-reported measures of wellbeing or quality of life. Only Randomised Controlled Trials published in peer-reviewed journals in English were eligible. Potential studies were screened and study characteristics and outcomes were extracted from eligible papers ndependently by two researchers. Where data allowed, meta-analysis was performed using a random effects model. Results Eight papers describing 5 trials with 593 participants were included, but only three studies were eligible for inclusion for meta-analysis. Of these, two aimed to improve asthma control and the third aimed to reduce the total dose of oral prednisolone without worsening control. Analyses with data from all three studies showed no significant differences and extremely high heterogeneity for both Asthma Quality of Life (AQLQ) (Standardised Mean Difference (SMD) 0.05; 95 % Confidence Interval (CI) 0.32 to −0.22: I2 96.8) and asthma control (SMD 0.21; 95 % CI −0.05 to .42; I2 = 87.4). The removal of the third study reduced heterogeneity and indicated significant improvement for both AQLQ (SMD 0.45; 95 % CI 0.13 to 0.77: I2 = 0.34) and asthma control (SMD 0.54; 95 % CI 0.22 to 0.86: I2 = 0.11). No evidence of harm was identified. Conclusion Digital self-management interventions for adults with asthma show promise, with some evidence of small beneficial effects on asthma control. Overall, the evidence base remains weak due to the lack of large, robust trials.